2012
DOI: 10.1038/onc.2012.328
|View full text |Cite
|
Sign up to set email alerts
|

The RUNX family in breast cancer: relationships with estrogen signaling

Abstract: The three RUNX family members are lineage specific master regulators, which also have important, context-dependent roles in carcinogenesis as either tumor suppressors or oncogenes. Here we review evidence for such roles in breast cancer (BCa). RUNX1, the predominant RUNX family member in breast epithelial cells, has a tumor suppressor role reflected by many somatic mutations found in primary tumor biopsies. The classical tumor suppressor gene RUNX3 does not consist of such a mutation hot spot, but it too seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 178 publications
5
91
0
1
Order By: Relevance
“…Runx2 has been shown to be expressed in metastatic breast cancer cells [19] and it promoted breast cancer cell invasion [18]. Expression of genes such as MMP-9, MMP-13, osteocalcin, and bone sialoprotein is regulated by Runx2 suggesting the role of Runx2 in breast cancer cell migration and invasion [20,21,[36][37][38]. The survival of breast cancer cell during metastasis also required Runx2 [22].…”
Section: Discussionmentioning
confidence: 96%
“…Runx2 has been shown to be expressed in metastatic breast cancer cells [19] and it promoted breast cancer cell invasion [18]. Expression of genes such as MMP-9, MMP-13, osteocalcin, and bone sialoprotein is regulated by Runx2 suggesting the role of Runx2 in breast cancer cell migration and invasion [20,21,[36][37][38]. The survival of breast cancer cell during metastasis also required Runx2 [22].…”
Section: Discussionmentioning
confidence: 96%
“…Factors that are crucial during embryogenesis are often hijacked during cancer progression, and RUNX2 is not an exception. RUNX2 is increasingly recognized in cancer biology for its oncogenic properties and a large number of articles link the deregulation of RUNX2 expression with progression and metastasization of different types of epithelial tumors (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Regulation of RUNX2 may occur at multiple levels and through multiple signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al pointed that RUNX3 rendered gastric cancer cells more prone to anticancer drugs through preventing expression of MDR-1(P-gp), MRP-1 (multidrug resistance protein-1) and Bcl-2 [31]. Its reduced expression has been demonstrated in several cancers including colorectal cancer, breast cancer and glioma [32][33][34]. The results of this study showed that miR-106a inhibited RUNX3 expression.…”
Section: Mir-106amentioning
confidence: 57%